ARAH MATA ANGIN PADA RUMAH BUGIS DAN IMPLIKASINYA TERHADAP KURIKULUM ILMU FALAK (Studi di Desa Talungeng Kecamatan Barebbo Kabupaten Bone) - HR, Sabriadi; Wakia, Nurul; Azzahrah, Nur Fatimah (UIN ALAUDDIN MAKASSAR, 2023)
This research discusses the cardinal directions of Bugis houses and their implications for Falak Science in Talungeng Village, Barebbo Subdistrict, Bone Regency. This type of research is field research using qualitative methods. The data collection methods are observation, interview, and documentation. The result of this research is that the methodology of determining the cardinal directions in Bugis houses in Talungeng Village, Barebbo Subdistrict, Bone Regency is by looking at the position of the sun, by looking at the place where the sun sets or rises. The implications of the use of cardinal directions in Bugis houses on Falak Science in Talungeng Village, Barebbo Subdistrict, Bone Regency indirectly have similarities with Falak Science as a branch of science related to celestial objects in applying its knowledge, one of which is the use of the sun as a method used by the people of Talungeng Village in determining cardinal directions. The implication of this research that the methodology of determining the cardinal directions in Bugis houses using the position of sunrise and sunset as one of the methods in determining the location of the cardinal directions needs to be done more in-depth research related to the level of accuracy and also the author hopes that religious leaders or Falak Science students themselves can pay more attention and socialize related to the actual Qibla direction.